Building in turbulent times. The work of Ingenieurs-Bureau Ingenegeren-Vrijburg (IBIV), 1936–1957 (Bulletin KNOB, 2016)
This article describes the work of Ingenieurs-Bureau Ingenegeren-Vrijburg (IBIV), an engineering firm located in Bandung (Indonesia). Founded by A.C. Ingenegeren and G.S. Vrijburg, IBIV was in operation from 1936 to 1957. In other words, the firm operated during the Dutch administration of the archipelago, under the Japanese occupation and in the newly independent Republic of Indonesia. What were the challenges for architects in the Dutch East Indies in general and for IBIV in particular? What were the design tasks and what did the designs look like? Did political changes affect the work and the organization of IBIV , and if so, which works illustrate these changes? The answers to these questions shed light on an intriguing aspect of Dutch architecture and architectural history.The scanty but well-documented materials (including images) relating to IBIV reveals a typologically and stylistically rich and varied body of work designed during a politically and socially turbulent period. ibiv worked for a wide variety of clients: Billiton, land development companies and Philips, as well as the University of Indonesia, the Indonesian government, Pusat Perkebunan Negara (National Agriculture Centre) and Perhimpunan Ilmu Alam Indonesia (Natural Science Association). It was not the major political upheavals (the Japanese occupation in 1942, the declaration of in dependence in 1945, the transfer of sovereignty in 1949), but a relatively minor issue (the political impasse over New Guinea in 1957) that led to the firm’s closure.IBIV appears to have transitioned effortlessly from a colonial to a post-colonial regime, from colonial to republican clients, and from colonial (Dutch East Indian) to post-colonial (Jenki) architecture. By studying IBIV ’s entire output, and so not just the colonial or the postcolonial work, it becomes clear that colonial and postcolonial are by no means self-contained entities. Professional developments did not cease when the colonial regime came to an end, any more than professional developments had to begin from scratch with the dawning of the post-colonial period.An examination of developments in the colonial and post-colonial periods from the perspective of professional continuity between the two periods, produces not necessarily simple, but certainly interesting insights into the colonial and post-colonial past. It shows that professional developments do not necessarily run parallel to political developments and as such argues for a (considerably) less rigid compartmentalization of research into colonial and post-colonial architecture. This initial study of the work and developments in and around IBIV shows what interesting results such an approach can produce.